GREEN SUKUK SEBAGAI INOVASI PEMBIAYAAN SYARIAH DALAM MENDUKUNG EKONOMI BERKELANJUTAN - Muhammad Haikal Fadillah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the role of green sukuk as an innovative Islamic financing instrument in supporting sustainable development and driving halal investment in Indonesia. As the world’s second-largest Muslim-majority country, Indonesia holds vast potential for developing the halal industry, which extends beyond food and beverages to encompass finance, tourism, fashion, and energy. Sukuk, as an Islamic capital market instrument, provides an alternative financing mechanism based on real assets in accordance with sharia principles, while green sukuk specifically funds environmentally friendly projects such as renewable energy, forest conservation, and waste management. This research applies a library study method by reviewing relevant literature, academic journals, and official documents related to the Islamic capital market, Islamic financing, and green sukuk. The findings indicate that green sukuk functions not only as a financial instrument but also as a social and ecological tool that reinforces the synergy between maqashid shariah and the Sustainable Development Goals (SDGs). Despite its promising prospects, the development of green sukuk in Indonesia still faces challenges in terms of limited regulations, incentives, and investor literacy. Therefore, this study recommends strengthening the regulatory framework, enhancing public and investor education, diversifying financed sectors, and fostering multi-stakeholder collaboration. Furthermore, future research should address existing gaps, including the effectiveness of green sukuk on national economic performance, comparative analysis with other sustainable instruments, and evaluations of projects funded by green sukuk to ensure greater contributions toward sustainable development.